Association of Genetic Variants of KCNJ11 and KCNQ1 Genes with Risk of Type 2 Diabetes Mellitus (T2DM) in the Indian Population: A Case-Control Study - Vasiuddin Khan; Amit Kumar Verma; Deepti Bhatt; Shahbaz Khan; Rameez Hasan; Yamini Goyal; Sowmya Ramachandran; Mohammed A. Alsahli; Arshad Husain Rahmani; Ahmad Almatroudi; M. Y. Shareef; Babita Meena; et al. (International Journal of Endocrinology)
Type 2 diabetes mellitus (T2DM) is a polygenic metabolic disease described by hyperglycemia, which is caused by insulin resistance or reduced insulin secretion. The interaction between various genetic variants and environmental factors triggers T2DM. The aim of this study was to find risk associated with genetic variants rs5210 and rs2237895 of KCNJ11 and KCNQ1 genes, respectively, in the development of T2DM in the Indian population. A total number of 300 cases of T2DM and 100 control samples were studied to find the polymorphism in KCNJ11 and KCNQ1 through PCR-RFLP. The genotype and allele frequencies in T2DM cases were significantly different compared to the control population. KCNJ11 rs5210 and KCNQ1 rs2237895 variants were found to be significantly associated with risk of T2DM in dominant (KCNJ11: OR, 2.07; 95% CI, 1.30–3.27; p−0.001; KCNQ1: OR, 2.33; 95% CI, 1.46–3.70; p−0.0003) and codominant models (KCNJ11: OR, 1.76; 95% CI, 1.09–2.84; p−0.020; KCNQ1: OR, 1.85; 95% CI, 1.16–2.95; p−0.009). We also compared clinicopathological characteristics between cases and control and observed a significant difference in all the parameters except HDL, gender, and family history. In this study, clinicopathological data with a carrier of a variant allele of both KCNJ11 and KCNQ1 genes were also analysed, and a significant association was found between the carrier of a variant allele with gender and PPG in KCNJ11 and with triglyceride in KCNQ1. We confirm the significant association of KCNJ11 (rs5210) and KCNQ1 (rs2237895) gene polymorphism with T2DM, indicating the role of these variants in developing risk for T2DM in Indian population.